Influence of kyphosis correction in thoracolumber spine on physical activity of children with infantile cerebral palsy - V. V. Umnov; I. E. Nikityuk; S. V. Vissarionov; O. A. Vereshchakina (Travmatologiâ i Ortopediâ Rossii, 2016)
Objective - to determinate the influence of kyphosis correction in thoracic spine on the ability to have vertical balance of the body in patients with cerebral palsy. Material and methods. The authors have performed a comprehensive survey of 17 patients with cerebral palsy aged from 6 to 17 years with the generated non-fixed "habitual" thoracolumbar kyphosis associated with joint contractures of the lower extremities. The analysis of the radiological data was carried out to determine the dependence of severity of kyphosis on the position of the body. The state of the vertical stability of children before and after thoracolumbar orthosis with body corset were evaluated by means of computed stabilometrics. Results. Radiological findings in all children have shown a normal correlation of changes in the degree of kyphosis - its reduction if there was an exclusion of the vertical load on the spine, as well as the trunk orthosis. In this case correction of sagittal profile of the spine occurred mainly due to the lumbar area. This feature of spinal biomechanics in patients with infantile cerebral palsy unpredictably reflected on the motor activity of patients. After correction of kyphosis with corset only 29.4% of the children surveyed with stabilometrics demonstrated the improvement in the function of maintaining the vertical position of the body. In 70.6% of patients the correction of sagittal profile of the spine has led to a deterioration of the vertical balance of the body. Negative dynamics of test research in this group presupposes the exhaustion of children’s adaptive capacity, which indicates the risk of developing abnormal compensatory reactions because of corset bracing. Conclusion. The advanced integrated observation of the patients with cerebral palsy can improve the prediction of outcomes in planning of the correction of kyphosis in thoracolumbar spine.